The author’s tendency in "The Naked Traveler 8": An Analysis of Travel Writing by Carl Thomson. - Nugroho, Aji Royan; Wulan, Retno (Journal of Translation, Linguistics and Literature, 2025)
This study aimed to reveal the subjectivity of The Naked Traveler 8 Novel by Trinity. Trinity’ Novel describes the eighty-eight-long journey that has been visited. The act of traveling can be conceptualized as a dynamic interplay between the dimensions of space and time, a perspective articulated by Trinity through the medium of travel writing. In order to analyze the data, the researchers employed the theory of travel writing proposed by Carl Thomson in his 2011 book Travel Writing. Furthermore, the concepts employed in this book draw upon Reporting the World, Revealing the Self, and Representing the Other. In summary, the study’s findings indicate the presence of a self-revelation of Trinity’s identity as an autobiographical travel writer in the novel, thereby emphasizing the subjective nature of her narrative. Moreover, the author narrates herself as an inferior eastern nation and a superior western nation.